The Impact of Brand Credibility and Brand Reputation on Brand Performance: An Empirical Analysis - Lingga Yuliana; Handika Arif Setiawan; Sasmiatin Irawan (University of Merdeka Malang, 2023)
Contemporary lifestyles have witnessed significant shifts due to the rapid pace of societal development. One notable change is the growing preference for instant noodles as a practical, tasty, and cost-effective food option. This research examines the interplay between key brand constructs: the influence of Brand Reputation on Brand Performance, the impact of Brand Credibility on Brand Reputation, and the influence of Brand Performance on Brand Credibility. Employing purposive sampling and a quantitative descriptive approach, this study surveyed 124 Indomie brand customers, aged 17 to 55. Primary data was collected via Google Form questionnaires and analyzed using Partial Least Squares (PLS) methodology with a five-point Likert scale for measurement. Results affirm all hypotheses. The first hypothesis regarding the positive link between brand credibility and brand performance is supported. Similarly, the second hypothesis reveals a positive connection between brand reputation and brand performance. Notably, the third hypothesis introduces a fresh perspective, demonstrating a positive correlation between brand credibility and brand reputation. In summary, this research unveils the complex dynamics in brand management. It highlights the critical roles of Brand Reputation, Brand Performance, and Brand Credibility in shaping consumer preferences and brand success. These insights hold significance for brand strategy and competitiveness in the marketplace.Top of Form